Electrochemical Proximity Assay of Platelet-Derived Growth Factor through Combined Surface Plasmon Resonance, Electrochemistry, and Fluorescence Spectroscopy Approach. (7th July 2017) - Zhou, Lang; Chin, Bryan A; Simonian, Aleksandr L.
Abstract : Platelet-derived growth factor (PDGF) is a potential cancer marker, which plays an important role in early detection of cancers. Due to its trace amounts in blood sample, it is difficult to be detected. Electrochemical Proximity Assay (ECPA) is an extremely flexible and sensitive technique with high potential for quantitation of a variety of proteins in clinical laboratory settings or at the point-of-care systems. In this study, we aim to use ECPA strategy on the PDGF recognition to achieve high sensitivity and specificity. In contrast to previous ECPA approach in which signals are only read out by electrochemical measurement, three characterization techniques including surface plasmon resonance, electrochemistry and fluorescence spectroscopy are combined together here so that these techniques are capable of cross-validating and complementing each other.